+0  
 
0
70
2
avatar

Solve the inequality x(x + 6) > 16 + 2x.

 Aug 12, 2021
 #1
avatar+2 
+1

x>-2+2sqrt(5)

 Aug 12, 2021
 #2
avatar+121056 
+1

x ( x + 6)  >   16  +  2x

 

x^2  +  6x  >  16  +  2x               rearrange    as

 

x^2 + 4x  -  16   >  0

 

Solve  this as an equality

 

x^2 +  4x  -  16  =  0               complete  the square on  x

 

x^2  +  4x  + 4   =  16  + 4

 

(x  + 2)^2  = 20            take  both roots

 

x + 2  =     ±sqrt 20

 

x  =  sqrt 20  - 2 ≈   2sqrt (5) - 2  ≈ 2.47          or          x  =  -sqrt 20  -  2  =  -2sqrt (5) - 2   ≈  -6.47

 

Note  that   the  intervals  that  possibly  solve  the original inequality  are  x  =

 

(-inf ,  ≈ -6.47)      or    ( ≈ -6.47 ,  ≈ 2.47)    or    ( ≈ 2,47 , inf)

 

If we let  x  =  0  ,the   middle interval  does not  solve  the original inequality

 

-

So.....the   solutions    are   ( -inf , -2sqrt (2) - 2 )   and  ( 2sqrt (5)   -2   ,  inf)

 

 

cool cool cool

 Aug 12, 2021

39 Online Users

avatar